CDR 2019
DOI: 10.20517/cdr.2019.49
|View full text |Cite
|
Sign up to set email alerts
|

Innate and adaptive resistance mechanisms to arginine deprivation therapies in sarcoma and other cancers

Abstract: Many cancers lack functional expression of the enzyme argininosuccinate synthetase 1 (ASS1) that is necessary for synthesis of L-arginine. These cancers must import arginine for survival and growth, and this reliance can be targeted by arginine-degrading extracellular enzymatic drugs, most commonly PEGylated arginine deiminase. These enzymes can become targets of the immune system, reducing their effectiveness, but PEGylation improves the in vivo stability. Arginine deprivation causes cell death in some cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Targeting exogenous arginine by arginine-metabolizing enzymes such as arginase, arginine decarboxylase and arginine deiminase (ADI) has received increasing attention as therapies to treat a variety of cancers [ 4 ]. There are a number of excellent reviews on this topic [ 5 , 6 , 7 ]. In this review, we will focus on recent progress in understanding arginine’s role in cancer metabolism as a signaling metabolite, an epigenetic regulator and an immunomodulator.…”
Section: Introductionmentioning
confidence: 99%
“…Targeting exogenous arginine by arginine-metabolizing enzymes such as arginase, arginine decarboxylase and arginine deiminase (ADI) has received increasing attention as therapies to treat a variety of cancers [ 4 ]. There are a number of excellent reviews on this topic [ 5 , 6 , 7 ]. In this review, we will focus on recent progress in understanding arginine’s role in cancer metabolism as a signaling metabolite, an epigenetic regulator and an immunomodulator.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the presence of hypoxia and low extracellular pH both appear to independently and synergistically enhance the silencing of ASS1. This was reported by Rogers et al who also hypothesized that the silencing of ASS1 occurs through multiple possible mechanisms such as the upregulated expression of miR-224-5p 27 . By silencing ASS1, a subsequent increase in cellular pH buffering is reported as increasing intracellular concentration of urea, glutamine, and glutathione are also observed 27 .…”
Section: Urea Cyclementioning
confidence: 67%
“…This was reported by Rogers et al who also hypothesized that the silencing of ASS1 occurs through multiple possible mechanisms such as the upregulated expression of miR-224-5p 27 . By silencing ASS1, a subsequent increase in cellular pH buffering is reported as increasing intracellular concentration of urea, glutamine, and glutathione are also observed 27 . Through the modulation of the urea cycle in this manner, Rogers et al additionally reports an inhibition of CAD.…”
Section: Urea Cyclementioning
confidence: 67%
“…Multiple studies have also shown that cancer cells can reactivate ASS1 expression and arginine biosynthesis when extracellular arginine becomes limited to support tumor growth. For example, ASS1-silenced tumors treated with arginine deiminase to eliminate extracellular arginine acquire resistance to such therapy by reactivation of ASS1 expression (Rogers and Van Tine, 2019; Rogers et al, 2021). In another example, reactivation of arginine biosynthesis was shown to be necessary to support metastasis of clear cell renal cancers to the arginine limited lung environment, whereas arginine biosynthesis was not necessary and inactive in the arginine-replete primary tumor (Sciacovelli et al, 2021).…”
Section: Discussionmentioning
confidence: 99%